ANALISIS INTENSI MAHASISWA DALAM MEMILIH UNIVERSITAS DARMA PERSADA (UNSADA) JAKARTA - Nani Dewi Sunengsih; Widiastuti Widiastuti; Ardi Winata (Jurnal Ilmiah Econosains, 2014)
ABSTRACTThe purpose of this study was to determine the intentions of the students chose the University of Darma Persada. This research was conducted at the University of Darma Persada, the population is students with formula Monion and Morrion with simple random sampling technique. Data retrieval technique using a questionnaire. The method used in this study are correlational and descriptive and inferential analisys with the help of Microsoft Excel and SPSS 19. Based on the results of the data analysis and discussion of the results, it can be concluded: (1) There is a positive influence on student attitudes toward the intentions of students choosing Darma Persada University. This means that an increase in student attitudes lead to increased student intentions choose Darma Persada University. (2) There is a positive effect of subjective norm on intention student students choose Darma Persada University. This means that an increase in the subjective norm resulted in increased student intentions Darma Persada University student chose. (3) There is a positive influence perceptions of student behavior control to the intention of the students select Darma Persada University. This means that an increase in perception of control student behavior resulting in increased student intentions choose Darma Persada University. (4) There is a positive influence on student attitudes, subjective norms, and perceived behavioral control together against the intentions of the students chose the University of Darma Persada. This means that an increase in student attitudes, subjective norms, and perceived behavioral control together lead to increased student intentions choose Darma Persada University.Keywords: intentions, student attitudes, subjective norms, perceived behavioral control